IMPACT OF AUDIO NARRATED ANIMATION ON STUDENTS' UNDERSTANDING AND LEARNING ENVIRONMENT BASED ON GENDER - Nasrudin, Ajeng Ratih (2014)
This study is titled the impact of audio narrated animation on students' understanding in learning human respiratory system based on gender. This study was conducted in eight grade of junior high school. This study aims to investigate the difference of students' understanding and learning environment at boys and girls classes in learning human respiratory system using audio narrated animation. Research method that is used is quassi experiment with matching pre-test post-test comparison group design. The procedure of study generally are: (1) preliminary study and learning habituation using audio narrated animation; (2) implementation of learning using audio narrated animation and taking data; (3) analysis and discussion. The result of analysis shows that there is significant difference on students' understanding and learning environment at boys and girls classes in learning human respiratory system using audio narrated animation, both in general and specifically in achieving learning indicators. The discussion related to the impact of audio narrated animation, gender characteristics, and constructivist learning environment. It can be concluded that there is significant difference of students' understanding at boys and girls classes in learning human respiratory system using audio narrated animation. Additionally, based on interpretation of students' respond that there is the difference increment of agreement level in learning environment.